2019
DOI: 10.1155/2019/1438793
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Sterile Wound Drapes in the Prevention of Surgical Site Infection in Thoracic Surgery

Abstract: Background. The rate of surgical site infections (SSIs) has decreased in parallel to advances in sterilization techniques. Such infections increase morbidity and hospitalization costs. The use of iodine-impregnated sterile wound drapes (SWDs) is recommended to prevent or reduce the incidence of these infections. However, there is a paucity of data regarding their use in thoracic surgical procedures. The aim of the present study was to evaluate the effectiveness of sterile wound drapes in the prevention of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The overall SSI rate was 1.5%, which reflects current literature rates mentioned above (6)(7)(8)(9)(10)(11). There is no consensus on criteria for the diagnosis of SSI (1,4,18). Up to 41 SSI definitions are reported in the literature.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The overall SSI rate was 1.5%, which reflects current literature rates mentioned above (6)(7)(8)(9)(10)(11). There is no consensus on criteria for the diagnosis of SSI (1,4,18). Up to 41 SSI definitions are reported in the literature.…”
Section: Discussionmentioning
confidence: 54%
“…SSIs are defined by the United States Centers for Disease Control and Prevention (CDC) as "an infection that occurs after surgery in the part of the body where the surgery took place" (15). Superficial SSIs involve only the skin and subcutaneous tissue while deep SSIs affect tissues under the skin like muscle, fascia, adjacent organs/space opened, or manipulated during the operation or foreign body (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the expected benefit for the patient, this report can and should serve as new arguments for public authorities to invest in the prevention of SSIs. An old and recent study on the cost-effectiveness analysis of preventive measures in surgery can be found in the literature (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Karapinar (2019) 20 and Hagen (1995) 13 have a high risk of bias as the intervention and control occurred over different time periods and Hagen (1995) 13 notes a significant increase in operative and cardiopulmonary bypass pump time in the control group. Yoshimura (2003) 15 has moderate confounding bias, as there was variation in the antiseptic skin preparation solution and the laparotomy incision approach.…”
Section: Bias Due To Confoundingmentioning
confidence: 99%